Protein Tyrosine Phosphatase 1B (PTP1B): A Potential Target for Alzheimer’s Therapy? - Vieira, Marcelo N. N.; Lyra e Silva, Natalia M.; Ferreira, Sergio T.; De Felice, Fernanda G. (Frontiers in Aging Neuroscience, 2017)
Despite significant advances in current understanding of mechanisms of pathogenesis in Alzheimer’s disease (AD), attempts at drug development based on those discoveries have failed to translate into effective, disease-modifying therapies. AD is a complex and multifactorial disease comprising a range of aberrant cellular/molecular processes taking part in different cell types and brain regions. As a consequence, therapeutics for AD should be able to block or compensate multiple abnormal pathological events. Here, we examine recent evidence that inhibition of protein tyrosine phosphatase 1B (PTP1B) may represent a promising strategy to combat a variety of AD-related detrimental processes. Besides its well described role as a negative regulator of insulin and leptin signaling, PTB1B recently emerged as a modulator of various other processes in the central nervous system (CNS) that are also implicated in AD. These include signaling pathways germane to learning and memory, regulation of synapse dynamics, endoplasmic reticulum stress and microglia-mediated neuroinflammation. We propose that PTP1B inhibition may represent an attractive and yet unexplored therapeutic approach to correct aberrant signaling pathways linked to AD.